Effect of four seminal plasma dilutions relating to ovulation rate, corpus luteum size and progesterone profile in alpacas - Reyna W., Iván (2015)
The study was carried out to evaluate the effect of four seminal plasma dilutions on ovulation rate and corpus luteum development in alpacas. Forty four non-lactating alpacas with the presence of a >7 mm dominant follicle detected by transrectal ultrasonography were selected. The animals were randomly distributed in five experimental groups: G1 (n=10) seminal plasma (SP) diluted 1:1 (v/v) with phosphate buffered saline (PBS); G2 (n=10) SP diluted 1:2 (v/v) with PBS; G3 (n=10) SP diluted 1:4 (v/v) with PBS; G4 (n=10) SP 1:8 (v/v) with PBS; and G5 (n=4) control group with PBS. A dose of 1.5 ml of the respective solution was intramuscularly administrated. Ovulation rate and corpus luteum size were evaluated at second and ninth day respectively (D0= day of treatment) through ultrasonography. Blood samples were taken on D0, D3, D6, D9 and D12 to determine serum progesterone levels by radioimmunoassay. The results indicated an ovulation rate of 100% in the treated groups and 0% in the control group. The corpus luteum size and serum progesterone levels did not show statistic differences. The results indicated that the ovulation inducing factor present in the seminal plasma has a powerful effect inducing ovulation even at a low dose.